Enlarging Post-Traumatic Forehead Mass in Liver Failure: A Case Report and Proposed Algorithm for the Treatment of Pseudoaneurysms of the Superficial Temporal Artery. Issue 3 (September 2022) - Aminzada, Amir; McNab, Andrea; Ferraro, Jennifer J.; Seu, Michelle; Tragos, Christina
Pseudoaneurysms of the superficial temporal artery are an exceedingly rare occurrence, and as such, there is limited data regarding their optimal management. In this paper we describe a case of post-traumatic superficial temporal artery pseudoaneurysm in a patient with alcohol-induced cirrhosis, treated with a combination of interventional radiologic and surgical methods. We also perform a review of the literature to identify the pathophysiology, diagnostic, and current treatment modalities of these entities. Finally, we propose a treatment algorithm for the optimal management of superficial temporal artery pseudoaneurysms under various circumstances.